Pelatihan Pembuatan Batik Kombinasi Cap dan Kuas Untuk Pengembangan Produk Home Decor pada Paguyuban Batik Giriarum - Nurcahyanti, Desy; Kristiandi, Kiki; Sari, Anisa Devita; Nurkasanah, Ayu Aisah; Rochimah, Ega Alfinna; Prayitno, Firda Ayu Hari; Grahan, Tahta keanu (Pakis Journal Institute, 2025)
The batik-making training, which combines stamping and brush techniques held in Girilayu, Matesih, Karanganyar, aims to enhance the skills of the Giriarum batik group members. As a center for traditional hand-drawn batik, Girilayu has significant potential to expand the variety of batik products it offers. In this training, participants are taught how to blend traditional hand-drawn batik techniques with modern methods such as stamping and brushing. The goal is for participants to create batik curtains that are not only aesthetically pleasing but also highly marketable. In addition to technical training, the training emphasizes the importance of business development aspects, including the selection of high-quality raw materials, the creation of innovative product designs, and the implementation of effective marketing strategies to enhance product competitiveness. With this knowledge, participants are expected to become more self-reliant and capable of expanding their batik market.